The cGAS-STING pathway: Post-translational modifications and functional implications in diseases. (December 2022) - Liu, Jun; Rui, Ke; Peng, Na; Luo, Hui; Zhu, Bo; Zuo, Xiaoxia; Lu, Liwei; Chen, Jixiang; Tian, Jie
Abstract: Recent studies have illustrated the functional significance of DNA recognition in the activation of innate immune responses among a variety of diseases. The cyclic GMP-AMP synthase-stimulator of interferon genes (cGAS-STING) pathway has been found to be modulated by post-translational modifications and can regulate the immune response via type I IFNs. Accumulating evidence indicates a pivotal role of cGAS-STING signaling, being protective or pathogenic, in the development of diseases. Thus, a comprehensive understanding of the post-translational modifications of cGAS-STING pathway and their role in disease development will provide insights in predicting individual disease outcomes and developing appropriate therapies. In this review, we will discuss the regulation of the cGAS-STING pathway and its implications in disease pathologies, as well as pharmacologic strategies to target the cGAS-STING pathway for therapeutic intervention. Graphical Abstract: ga1 Highlights: Activation of cGAS-STING is regulated by post transcriptional modifications (PTMs). Cell-free DNA (cfDNA)-elicited IFN is involved in a variety of pathological processes via cGAS-STING signaling. Therapies targeting cGAS-STING shows efficacies in infection, autoimmune diseases and tumors.